التربية الخاصة في سلطنة عمان: Special Education in the Sultanate of Oman - Nasser Hinai , Musaab Salim; Hussein Amzat, Ismail; Abd. Hamid , Siti Rafiah (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث هدفت الدراسة إلى تعرف واقع منظومة التربية الخاصة بسلطنة عمان ودورها في رعاية ذوي الاحتياجات الخاصة، وضع استراتيجية مقترحة لتطور منظومة التربية الخاصة بالسلطنة، واستخدمت الدراسة المنهج الوصفي التحليلي لمناسبته لطبيعة الدراسة، وتوصلت الدراسة إلى وضع استراتيجية مقترحة لتطوير منظومة التربية الخاصة بسلطنة عمان. ABSTRACT The study aimed to identify the current state of the special education system in the Sultanate of Oman and its role in supporting individuals with special needs. It also sought to propose a strategy for the development of the special education system in the Sultanate. The study employed the descriptive-analytical method due to its suitability for the nature of the research. The study concluded with a proposed strategy for the development of the special education system in the Sultanate of Oman.